2017
DOI: 10.1111/ijlh.12743
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an automated chemiluminescent assay to a manual ELISA assay for determination of von Willebrand Factor collagen binding activity on VWD plasma patients previously diagnosed through molecular analysis of VWF

Abstract: Introduction: The correct diagnosis and classification of VWD (von Willebrand dis-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Ten addressed diagnostic test accuracy for types 2A and 2B 59,85-93 and 6 for type 2M. [87][88][89][90]92,93 For types 2A and 2B, the sensitivity of VWF:CB/VWF:Ag was 0.90 (95% CI, 0.78-0.96) and specificity was 0.95 (95% CI, 0.89-0.98), vs a sensitivity of 0.90 (95% CI, 0.90-0.99) and specificity of 0.97 (95% CI, 0.94-0.99) for multimers. For type 2M VWD, the sensitivity of VWF:CB/VWF:Ag was 0.98 (95% CI, 0.96-1.00) with a specificity of 0.99 (95% CI, 0.98-1.00), vs a sensitivity of 0.86 (95% CI, 0.73-0.98) and a specificity of 0.97 (95% CI, 0.94-0.99) for multimers.…”
Section: Remarkmentioning
confidence: 99%
“…Ten addressed diagnostic test accuracy for types 2A and 2B 59,85-93 and 6 for type 2M. [87][88][89][90]92,93 For types 2A and 2B, the sensitivity of VWF:CB/VWF:Ag was 0.90 (95% CI, 0.78-0.96) and specificity was 0.95 (95% CI, 0.89-0.98), vs a sensitivity of 0.90 (95% CI, 0.90-0.99) and specificity of 0.97 (95% CI, 0.94-0.99) for multimers. For type 2M VWD, the sensitivity of VWF:CB/VWF:Ag was 0.98 (95% CI, 0.96-1.00) with a specificity of 0.99 (95% CI, 0.98-1.00), vs a sensitivity of 0.86 (95% CI, 0.73-0.98) and a specificity of 0.97 (95% CI, 0.94-0.99) for multimers.…”
Section: Remarkmentioning
confidence: 99%
“…VWF:CB is usually tested by an ELISA but recently an automated and rapid chemiluminescence method has become available. 61 Typically, a mixture of type I or type III collagen is used because it increases specificity. 62 The A3 VWF domain binds type I and type III collagen, while the A1 domain binds type IV and type VI collagen, but assays testing this latter interaction are not widely available.…”
Section: Laboratory Testing For Vwdmentioning
confidence: 99%
“…7 The collagen binding assay (VWF:CB) reveals the adhesion capacity of HMW multimers of VWF to collagen. 8 This assay is useful to reduce the misleading diagnosis of VWD and should be widely adopted in hematology laboratories. Favaloro et al showed that limiting the assays to FVIII:C, VWF:Ag, and VWF:RCo can induce a high background diagnostic error rate (approximately 20% error rate for type 1 VWD misidentified as type 2 VWD, approximately 30% for type 2 VWD misidentified as type 1 VWD, and nearly 5% for normal samples being identified as being from VWD patients).…”
Section: Vwd Is Associated With Genetic Defects In the Vonmentioning
confidence: 99%
“…Additionally, analysis of VWF:RCo/VWF:Ag is performed to predict quantitative (ratio ≥0.6) and qualitative (ratio <0.6) VWF deficiencies . The collagen binding assay (VWF:CB) reveals the adhesion capacity of HMW multimers of VWF to collagen . This assay is useful to reduce the misleading diagnosis of VWD and should be widely adopted in hematology laboratories.…”
Section: Introductionmentioning
confidence: 99%